PENDIDIKAN KARAKTER BAGI GENERASI MASA KINI - Primasari, Dwi Ammelia Galuh; Dencik, Dencik; Imansyah, M. (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Character Education has become a hot topic today. Character Education has been transformed into something that is considered urgent in the millennial era. The government has realized that the younger generation is a valuable asset that will fill and determine the progress of the nation, so that it needs to be safeguarded and developed in accordance with the goals of the nation's education. Starting from that, this study aims to provide an overview of Character Education for the younger generation in the globalization and digital era today. This study uses a qualitative-descriptive approach with a method of observing data from existing facts and documents. As a result, it was concluded that in the current era of globalization / digital character education is very important as an effort to shape the character of a generation of people who are not only skilled and intelligent, but also noble. Despite facing various problems in the implementation process, but with the collaboration of various parties, the hope of forming intelligent Indonesian people and character in accordance with the Pancasila and religious values can be realized.